Simultaneous measurement of adenosine triphosphate release and aggregation potentiates human platelet aggregation responses for some subjects, including persons with Quebec platelet disorder - Hayward, Catherine P. M.; Moffat, Karen A.; Castilloux, Jean-Francois; Liu, Yang; Seecharan, Jodi; Tasneem, Subia; Carlino, Stephen; Cormier, Anik; Rivard, Georges E. (Thrombosis and Haemostasis, 2012)
Platelet aggregometry and dense granule adenosine triphosphate (ATP) release assays are helpful to diagnose platelet disorders. Some laboratories simultaneously measure aggregation and ATP release using Chronolume®, a commercial reagent containing D-luciferin, firefly luciferase and magnesium. Chronolume® can potentiate sub-maximal aggregation responses, normalising canine platelet disorder findings. We investigated if Chronolume® potentiates human platelet aggregation responses after observing discrepancies suspicious of potentiation. Among patients simultaneously tested by light transmission aggregometry (LTA) on two instruments, 18/43 (42%), including 14/24 (58%) with platelet disorders, showed full secondary aggregation with one or more agonists only in tests with Chronolume®. As subjects with Quebec platelet disorder (QPD) did not show the expected absent secondary aggregation responses to epinephrine in tests with Chronolu-me®, the reason for the discrepancy was investigated using samples from 10 QPD subjects. Like sub-threshold ADP (0.75 μM), Chronolume® significantly increased QPD LTA responses to epinephrine (p<0.0001) and it increased both initial and secondary aggregation responses, leading to dense granule release. This potentiation was not restricted to QPD and it was mimicked adding 1–2 mM magnesium, but not D-luciferin or firefly luciferase, to LTA assays. Chronolume® potentiated the ADP aggregation responses of QPD subjects with a reduced response. Furthermore, it increased whole blood aggregation responses of healthy control samples to multiple agonists, tested at concentrations used for the diagnosis of platelet disorders (p values <0.05). Laboratories should be aware that measuring ATP release with Chronolume® can potentiate LTA and whole blood aggregation responses, which alters findings for some human platelet disorders, including QPD.
Keywords: Inherited / acquired platelet disorders; inherited / acquired platelet pathology; clinical studies